TAFSIR FILOSOFIS MULLÄ€ á¹¢ADRÄ€ Analisis Materi Filosofis Kitab TafsÄ«r Ä€yat al-KursÄ« - Musadad, Asep Nahrul (SUHUF, 2017)
The main purpose of this paper is to describe an intersection between QurÃ¢â‚¬â„¢anic exegetical tradition and Islamic philosophy, with special reference to the TafsÃ„Â«r Ã„â‚¬yat al-KursÃ„Â«, one of the MullÃ„Â Ã¡Â¹Â¢adrÃ„ÂÃ¢â‚¬â„¢s works on QurÃ¢â‚¬â„¢anic commentary. Ã¡Â¹Â¢adrÃ„Â is one of the representative exponents of a philosophical school called Ã¡Â¸Â¥ikmah (theosophy), which developed after Ibn Rusyd period in the eastern part of the Islamic world. In order to know the unique form of interaction between Al-QurÃ¢â‚¬â„¢an and Islamic philosophy, TafsÃ„Â«r Ã„â‚¬yat al-KursÃ„Â« is a representative work to be explored, particularly by studying philosophical materials in it. This research shows that the book was written when MullÃ„Â Ã¡Â¹Â¢adrÃ„Â had just completed the ascetic phase in Kahak, along with the tension happened between exoteric and esoteric groups. TafsÃ„Â«r Ã„â‚¬yat al-KursÃ„Â« is also one of two earliest Ã¡Â¹Â¢adrÃ„ÂÃ¢â‚¬â„¢s works on QurÃ¢â‚¬â„¢anic commentary. In addition to previous commentaries, the material sources of this book consist of sufism, kalam (dialectics), and philosophy. In the philosophical frame, this book encompasses metaphysical, cosmological and eschatological issues, as well as some of the QurÃ¢â‚¬â„¢anic sciences issues discussed in an onto-epistemological way.